Switching effect in the magnetization response in a superconducting specimen of Ca3Rh4Sn13. (6th April 2016) - Suresh Babu, M; Thamizhavel, A; Ramakrishnan, S; Grover, A K; Pal, D
Abstract: The isofield magnetization measurements in a superconducting single crystal of Ca3 Rh4 Sn13 show the paramagnetic magnetization response in a specific region of the magnetization curve while field cooling under various experimental conditions. Such a response in the specific region is found to be multivalued/metastable, which can be manipulated in a characteristics manner by altering the experimental conditions. The controlled switching of magnetization between widely differing values including the change in sign of magnetization, has application potential in magnetic switching and binary memory devices.